Romantic orientalism and 19th century American literature : a critical analysis of islamic concepts in selected poems of Edgar Allan Poe - Raheem, Faatimah Salmyyah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This qualitative study attempts to discover Islamic concepts in selected poems of Edgar Allan Poe using Mohammed Sharafuddin's Realistic Orientalism framework. This is achieved by cross-examining main concepts found in Poe's poems with George Sale's English translation of the Qur'an. Prior to this analysis, the study also examines the possible main influences of Islam on Poe to substantiate the study. The study finds that there is limited documented evidence on Poe's exposure to Islamic sources. The study identifies the effects of the Barbary Wars, American travel writings, British Romantic poetry and George Sale's English translation of the Qur'an as major influences. Additionally, the author proposes that Poe's brother, William Henry Leonard Poe, also exerted a more personal influence on his interest in the Islamic Orient. However, analyses of the selected poems indicate varying degrees of similarities with Sale's translation of the Qur'an. The findings reveal that Poe is influenced—in descending order—by the Islamic concepts of death, the afterlife, the human soul and heart, divine inspiration, supernatural entities and ethereal places in the Qur'an. Other possible Islamic influences may have come from a biography of Prophet Muhammad, the Hadith and Sufi Literature. This concludes that Poe was indeed influenced by Sale's English translation of the Qur'an, at least one biography of Prophet Muhammad and other sources of Islam yet to be verified.